Obesogenic clusters: excess body weight-related lifestyle behaviors in schoolchildren - Dartagnan Pinto Guedes; Robson Recalcatti; Marcelo Seiji Missaka (Revista Brasileira de Cineantropometria e Desempenho Humano, 2023)
The objective of the study was to identify the existence of clusters in multiple lifestyle behaviors, including fruits/vegetables intake, sweetened products/soft drinks intake, sleep duration, physical activity and sedentary behavior. In sequence, the association between identified clusters and excess body weight in schoolchildren was examined. This was a cross-sectional school-based epidemiological study with approximately 17 thousand schoolchildren aged 4-20 years who participated in the Parana Health Project. Questionnaire was applied with structured questions to collect lifestyle behaviors. Excess body weight was identified through body mass index. Cluster analysis was performed to identify sex-specific clusters of multiple lifestyle behaviors. Analysis of covariance and logistic regression were used to analyze associations between clusters and excess body weight. Five clusters were identified in both sexes. Schoolchildren in the cluster characterized by lower fruits/vegetables intake and greater time spent in sedentary behavior showed close to twice the chance of having excess body weight compared to their peers in the reference cluster (girls: OR=1.98 [1.41-2.93]; boys: OR=1.94 [1.39-3.01]). In the case of schoolchildren in the cluster characterized by high sweetened products/soft drinks intake and shorter sleep duration, the chances of having excess body weight were 69% in girls (OR=1.69 [1.23-2.67]) and 73% in boys (OR=1.73 [1.25-2.91]). In conclusion, high fruits/vegetables intake, low sweetened products/soft drinks intake, longer sleep duration and less sedentary behavior was considered the most effective combination for maintaining a healthy body weight in the sample of schoolchildren.